Pengaruh Undervaluation, Free Cash Flow, Leverage dan Profitabilitas Terhadap Stock Buyback Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021 - Safitri, Maulida (Jurnal Manajemen Akuntansi (JUMSI), 2025)
Stock buyback or share buyback is a corporate action in which a company buys back company shares that have been circulated to the public. This study aims to examine and analyze the effect undervaluation, free cash flow, leverage and profitability against stock  buyback for companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This research is included in quantitative research. The population of this study are companies listed on the Indonesia Stock Exchange for the period 2017 – 2021. The sampling technique uses the purposive sampling with a total sample of 46 companies. The analytical method used is descriptive statistics, classical assumption test, multiple linear regression analysis, and goodness of fit model. The research results show undervaluation, free cash flow, leverage and profitability has no effect on stock buyback for companies listed on the Indonesia Stock Exchange for the 2017-2021 period.